Illegal immigration in Algeria between reasons and solutions - Ghazala, Zubair (Journal of Humanities & Social Sciences, 2018)
The phenomenon of illegal immigration or "AL HARGA" as defined in Algerian society is one of the most difficult social phenomena that despite all the awareness and security efforts to stop it, continues to escalate due to the conflict between the living standard, On one hand, and because of the material and moral marginalization that unfortunately extended to the best people of this country on the other.Even though causes may vary, but the result in general has almost become the same as the wholesale boats of death, people flee from their homeland that is supposed to be the refuge and safe place, not a place to escape from.Therefore, we saw that it is very important to address this phenomenon, or rather the external social scourge of our Algerian society, which was not abandoned by its sons at the height of wars with the French destitute nor at the height of the black decade crisis of the nineties, Why escape now after the restoration of sovereignty? And why can’t we overcome the internal crisis by bringing peace and security?The aim of this study as researchers on issues of interest to the community is to highlight the imbalance leading to the continuous and frightening increase in the Algerian youth's desire for the adventures of illegal immigration in different ways, despite their prior knowledge of the deadly dangers that surround them. Great readiness to stay in their community in the event of a decent life.
Keywords: migration; Illegal; Reasons; Solution; Algeria